Is it Safe for a Mother Infected with Hepatitis B Virus to Breastfeed Her Baby? - Uddin Ahmed, ASM Nawshad; Hoque, Md Mahbubul (Bangladesh Journal of Child Health, 2012)
One third of the worlds population has been infected by the hepatitis B virus (HBV), causing an enormous burden of chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Hepatitis B virus is transmitted through contact with blood and blood products, by sexual contact, through close contact between children (horizontal transmission), or by perinatal transmission from a carrier mother to her baby. In Asia, perinatal transmission is the major mode of transmission and those who become infected perinatally with HBV are most likely to develop chronic infection. The question of whether breastfeeding by HBV-positive mothers is an additional mechanism by which infants may acquire HBV infection, has been asked for many years. Although small amounts of hepatitis B surface antigen (HBsAg) have been detected in some samples of breast milk, there is no evidence that breastfeeding by HBV-carrier mothers increase the risk of mother-to-child transmission of HBV. Infants born to known hepatitis B positive women should receive hepatitis B immune globulin (HBIG) and hepatitis B vaccine, effectively eliminating any theoretical risk of transmission through breastfeeding. However, neither screening of pregnant women for HBV infection nor use of HBIG is feasible in most developing countries. Routine immunization of infants with hepatitis B vaccine is therefore recommended by the World Health Organization. Bangladesh has already included hepatitis B vaccine as part of routine childhood immunization in EPI program since 2003. Also the risk must be balanced against the increased risk of morbidity and mortality due to malnutrition and diarrheal or other infectious diseases associated with replacement feeding. Malnutrition is responsible, directly or indirectly, for 6.5 million under 5 deaths annually. Thus, even where HBV infection is highly endemic and immunization against HBV is not available, breastfeeding remains the recommended method of feeding. DOI: http://dx.doi.org/10.3329/bjch.v35i1.10369 BJCH 2011; 35(1): 20-25